Wharton on making decesions (John Wiley & Sons, 2001)
Wharton on Making Decisions provides a unique blend of theory and practical experience. The authors’ insights are at many times humorous, always instructive, and definitely thought provoking. This book should be recommended reading for decision makers in today’s fast-moving world where alternative choices are increasing in number, complexity, and importance